Patient-reported 1-year outcome not affected by body mass index in 3, 327 total knee arthroplasty patients. (4th July 2019) - Overgaard, Anders; Lidgren, Lars; Sundberg, Martin; Robertsson, Otto; W-Dahl, Annette
Abstract : Background and purpose — Patient-reported outcome (PRO) in total knee arthroplasty (TKA) patients with high body mass index (BMI) is controversial. We compared pain, function, quality of life, general health, and satisfaction among different BMI categories preoperatively and 1 year after primary TKA. Patients and methods — 4, 318 patients were operated with a TKA for knee osteoarthritis in the Region of Skane in 2013–2015. In all, 3, 327 patients (77%) had complete PRO data and information on BMI and were included. Preoperatively the patients filled in the Knee injury and Osteoarthritis Outcome Score (KOOS) and EQ-VAS (general health). 1 year postoperatively the same questionnaires were filled in together with a question asking whether they were satisfied with the surgery. Information on age, sex, BMI, and ASA grade were obtained from the Swedish Knee Arthroplasty Register. Each patient was classified as Outcome Measures in Rheumatology– Osteoarthritis Research Society International (OMERACT–OARSI) responder or not based on a combination of absolute and relative changes in scores. Welch's t-test and a chi-square test were used in the statistical analysis. Results — Both preoperatively and 1 year postoperatively the obese patients reported somewhat worse scores than the normal weight and overweight. The differences were small with 1 exception, the KOOS sport- and recreation function postoperatively, where normal-weight and overweight patients reported fewer problems than obese patients with a BMI over 35 (40 and 39 points vs. 31 points, p < 0.001). Similar proportions of patients were satisfied and categorized as OMERACT–OARSI responders in the different BMI categories. Interpretation — The degree of improvement in PROs 1 year after TKA surgery does not seem to be affected by BMI.